2014
DOI: 10.1007/s10620-014-3174-7
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Diagnostic Codes for Identifying Patients with Ulcerative Colitis and Crohn’s Disease in the Veterans Affairs Health Care System

Abstract: Single ICD-9 codes are inadequate to accurately define IBD patients; however, ICD-9 code algorithms can be used to identify patients with UC or CD with high positive predictive value. The 2 code, at least 1 outpatient code algorithm was observed to have a high PPV and low miss rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 13 publications
0
47
0
Order By: Relevance
“…ICD-9-CM coding has demonstrated accuracy in IBD 47,48 and other studies of gastrointestinal disorders, 49 however this remains a concern in our population given mixed performance within studies of patients with IBD in the Veterans Affairs system. 50,51 There also exists the potential for underdiagnosis of other risk factors, particularly tobacco use and obesity. 52 …”
Section: Discussionmentioning
confidence: 99%
“…ICD-9-CM coding has demonstrated accuracy in IBD 47,48 and other studies of gastrointestinal disorders, 49 however this remains a concern in our population given mixed performance within studies of patients with IBD in the Veterans Affairs system. 50,51 There also exists the potential for underdiagnosis of other risk factors, particularly tobacco use and obesity. 52 …”
Section: Discussionmentioning
confidence: 99%
“…Coding may be more complete in parts of the US health care system in which reimbursement depends on the codes assigned. Previous studies have found that diagnosis codes assigned in VA administrative data accurately represent the prevalence of some conditions (eg, post-traumatic stress disorder and diabetes) but underestimate others (eg, ulcerative colitis and chronic kidney disease) [20][21][22][23][24][25][26][27][28][29][30]. We are unaware of any study evaluating the accuracy of VA coding of the diagnoses and procedures needed to assess appropriateness of LS MRI orders.…”
Section: Discussionmentioning
confidence: 99%
“…VA users with IBD were identified using a previously validated ICD-9 diagnosis code algorithm [7] of at least 2 VA encounters for UC or CD with at least 1 IBD-associated VA outpatient encounter from the fiscal years 1998 to 2012. The date of the first documentation of an IBD code served as the IBD index date.…”
Section: Methodsmentioning
confidence: 99%